Upaya Pembentukan Habitus Remaja (Studi Kasus di Panti Sosial Bina Remaja Taruna Jaya 1) - Wanda Marsella; Rizki Setiawan; Yustika Irfani Lindawati (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2024)
The focus of this research is efforts to form habitus for adolescent at Panti Sosial Bina Remaja Taruna Jaya 1. The aims of this research are 1) To find out efforts to form habitus for foster adolescent at Panti Sosial Bina Remaja Taruna Jaya 1, 2) To find out forms of adaptation for foster adolescent at Panti Sosial Bina Remaja Taruna Jaya 1. This type of research uses a case study method with a qualitative approach. Data collection techniques use observation, interviews and documentation. The informant selection technique used was a purposive technique, in this study the informants selected were 6 (six) family referral foster youth and 4 (four) staff of Panti Sosial Bina Remaja Taruna Jaya 1. The results of the research showed that 1) The habitus that wants to be formed at Panti Sosial Bina Remaja Taruna Jaya 1 is a healthy habitus, professional habitus, intellectual habitus, collaborative habitus, social habitus, spiritual habitus. 2) The environment of Panti Sosial Bina Remaja Taruna Jaya 1 is an arena where there is doxa, so that there is symbolic violence during the habitus formation process at Taruna Jaya 1 PSBR. In the end, this doxa becomes orthodoxa in the form of the success of foster youth in adapting at Panti Sosial Bina Remaja Taruna Jaya 1 and in an environment that has similar 'rules of the game'. The description of the successful adaptation of foster youth can be seen from 4 (four) aspects: emotional aspects, intellectual aspects, spiritual aspects, social aspects.